Case Report: Selective hepatic resection guided by indocyanine green short-wave infrared fluorescence imaging in a dog with multifocal liver lesions - Jang, Soyoung; Kim, Yujin; Kim, Sunyoung; Lee, Sungin (Frontiers in Veterinary Science, 2025)
An 11-year-old female spayed Maltese was presented with multiple hepatic masses identified on abdominal ultrasonography and triphasic computed tomography. Lesions were distributed across the left lateral, left medial, quadrate, and caudate liver lobes. A large multicystic mass originating from the left lateral lobe was considered at high risk of rupture, leading to the palliative surgery. Indocyanine green (ICG) was intravenously administered at a dose of 0.5 mg/kg 24 h prior to surgery. During laparotomy, the liver was assessed using a short-wave infrared (SWIR) fluorescence imaging system. Only the mass arising from the left lateral lobe exhibited ICG fluorescence, while no fluorescence was detected in the other lesions. Based on these findings, a left lateral lobectomy including the ICG-positive mass was performed, and punch biopsies were taken from the non-fluorescent lesions in other lobes. Histopathologic examination confirmed the mass from the left lateral lobe as combined hepatocellular carcinoma-cholangiocarcinoma with tumor-free margins. The biopsied lesions were diagnosed as vacuolar hepatopathy. Follow-up evaluation over 6 months revealed no evidence of metastasis. This case demonstrates the potential clinical utility of ICG-SWIR fluorescence imaging in not only detecting and achieving complete resection of tumors, but also supporting real-time intraoperative decision-making, which enables selective resection of malignant tissue while sparing benign lesions.